Five new subterranean amphipods of the genus Pseudocrangonyx from Korea (Crustacea, Amphipoda, Pseudocrangonyctidae) - Tae Won Jung; Jong Guk Kim; Min-Seop Kim; Seong Myeong Yoon (ZooKeys, 2020)
Although the majority of the species belonging to the genus Pseudocrangonyx Akatsuka & Komai, 1922 are found among the subterranean fauna of eastern Asia, the taxonomic knowledge is very poor and only four species have been recorded in Korea. In this study, the morphology of the stygobitic pseudocrangonyctid amphipods from Korean subterranean waters was examined and five new species were identified: Pseudocrangonyx concavus sp. nov. has a characteristic emarginated posteroventral margin of epimeral plate 3; Pseudocrangonyx gracilipes sp. nov. differs from other pseudocrangonyctids by the slender and elongated pereopods and more produced posterodistal corner of epimeral plate 3. Pseudocrangonyx crassus sp. nov. shows the expanded peduncular articles and a reduced flagellum of antenna 2. Pseudocrangonyx minutus sp. nov. is distinguished by more reduced pleopod articles compare to other pseudocrangonyctids. Pseudocrangonyx villosus sp. nov. has the more setose bases of pereopods 3 and 4. Detailed descriptions and illustrations are presented for these five new species.